Competitive procurement design: Evidence from regional passenger railway services in Germany - Matthias Hunold; Christoph Wolf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We study competitive awarding procedures of short haul railway passenger services in Germany from 1995 to 2011 by means of a newly collected data set. In particular, we use regression techniques to investigate the determinants of the number of bidders, the identity of the winning bidder and the subsidy level. We find that there are more bidders when the contract duration is high and the revenue risk low. The dominant operator is more likely to win contracts if it is the incumbent, the network is large, the contract duration is high, when used rolling stock is admitted and when there are few other bidders.
urn:nbn:de:bsz:180-madoc-331703
Keywords: D44; H57; L92; 330; competitive tendering; market entry; networks; public procurement; railroads